2018
DOI: 10.1111/pce.13414
|View full text |Cite
|
Sign up to set email alerts
|

Computational models evaluating the impact of sieve plates and radial water exchange on phloem pressure gradients

Abstract: The sugar conducting phloem in angiosperms is a high resistance pathway made up of sieve elements bounded by sieve plates. The high resistance generated by sieve plates may be a trade-off for promoting quick sealing in the event of injury. However, previous modeling efforts have demonstrated a wide variation in the contribution of sieve plates towards total sieve tube resistance. In the current study, we generated high resolution scanning electron microscope images of sieve plates from balsam poplar and integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 43 publications
2
16
1
Order By: Relevance
“…The model reproduced experimentally measured sap sucrose concentrations and velocities well. Interestingly, our model indicated that high viscosity in the phloem was the major resistance factor in potato, in contrast to sieve‐tube geometry reported in earlier work on larger plants (Stanfield, Schulte, Randolph, & Hacke, 2019; Thompson & Holbrook, 2003). This result is consistent with the higher sucrose concentration (Jensen et al, 2013), shorter stem‐length, and higher flow velocity (Comtet et al, 2017; Windt et al, 2006) reported for herbaceous species, suggesting it might be a general property of small herbaceous crop species.…”
Section: Discussioncontrasting
confidence: 87%
“…The model reproduced experimentally measured sap sucrose concentrations and velocities well. Interestingly, our model indicated that high viscosity in the phloem was the major resistance factor in potato, in contrast to sieve‐tube geometry reported in earlier work on larger plants (Stanfield, Schulte, Randolph, & Hacke, 2019; Thompson & Holbrook, 2003). This result is consistent with the higher sucrose concentration (Jensen et al, 2013), shorter stem‐length, and higher flow velocity (Comtet et al, 2017; Windt et al, 2006) reported for herbaceous species, suggesting it might be a general property of small herbaceous crop species.…”
Section: Discussioncontrasting
confidence: 87%
“…One way the membrane can counteract this loss of conductivity may be from upregulating aquaporin abundance in the plasma membrane. More aquaporin abundance means greater rates of radial water flows into the sieve tubes [12], which have the effect of decreasing viscosity and lowering pressure gradients. In effect, this upregulation of aquaporins in the membrane may be a way to counteract some aquaporin gating via a temporary pressure surge.…”
Section: Discussionmentioning
confidence: 99%
“…However, the intervening transport phloem which connects source and sink is often neglected due to the difficulty of accessing this deeply embedded tissue. The importance of the transport phloem for influencing long-distance translocation cannot be understated, as it may act as an exchange point for water and nutrients [11], which has been modeled to significantly influence pressure profiles [12].…”
Section: Introductionmentioning
confidence: 99%
“…This is surprising as increased phloem structural resistance should make the plant more vulnerable to run-away viscosity, especially during drought. Structural aspects of the phloem that contribute to resistance may be in the form of its cell diameter and the porosity of their end walls (sieve plates) (e.g., Mullendore et al 2010, Stanfield et al 2019). In addition, the scaling of the conduits from source-sink may also play a role to minimize resistance and maintain adequate pressure gradients in both leaves and stems (Carvalho et al 2017, Savage et al 2017; this scaling increases in magnitude as pathway resistance per unit length lowers in taller trees to maintain flow at great heights (Clerx et al 2020).…”
Section: Introductionmentioning
confidence: 99%